Análise dos sistemas de produção dos estabelecimentos rurais do município de Palmital/SP em busca de estratégias para o desenvolvimento rural - Bianchi, Vinícius Rafael [UNESP] (2015)
This study aimed to make an analysis of agrarian systems of the city of Palmital / SP, located in the center west region of São Paulo, more precisely in the Middle Paranapanema, through a historical context, landscape analysis and of existing studies on it. Then it was established the typology of farmers of the municipality and of production systems by them. Such an approach is based on a systemic approach, guided the premises of the diagnosis of agrarian systems tool. Defined typologies, the different forms of income generation of productive systems in that locality were established. Assuming the importance of equity in the maintenance and reproduction of agricultural production systems by means of multivariate statistical analysis (multiple regression model) were analyzed what are the factors that interfere positively or negatively in the agricultural income of farmers. Data collection for analysis was done through a survey form applied to a stratified sample of farmers, proportional (to the condition of the farm). All data collected are between the period August 2013 to July 2014. These results point allowed the transformation of agrarian systems of the study area and the presence of different types of farmers: employers and family, with diversification in these production systems, respectively; in cases in which it showed those factors that influence the result obtained in agricultural income positive or negative way. Anyway, enabling elaborate proposals for rural development to the city of Palmital / SP.